2019
DOI: 10.1016/j.jnucmat.2018.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Defect evolution in burnable absorber candidate material: Uranium diboride, UB2

Abstract: The stability, diffusivity and clustering behaviour of defects in uranium diboride (UB 2) was investigated in light of the potential application as a burnable absorber in nuclear fuel. UB 2 was found to accommodate limited deviations from stoichiometry, which should be a consideration when manufacturing and operating the material. Self-diffusivity of both U and B was found to be sluggish (10 −14 cm 2 /s for B and 10 −19 cm 2 /s for U at 2000 K) and highly anisotropic, with migration along the basal planes bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
2
7
0
1
Order By: Relevance
“…Projector augmented-wave potentials [15] were used with the GGA-PBE exchange correlation [16] supplied with the software. In accordance with the results from Burr et al [7], no Hubbard parameter was applied to the U f-electrons.…”
Section: Atomic Scale Modellingsupporting
confidence: 61%
See 1 more Smart Citation
“…Projector augmented-wave potentials [15] were used with the GGA-PBE exchange correlation [16] supplied with the software. In accordance with the results from Burr et al [7], no Hubbard parameter was applied to the U f-electrons.…”
Section: Atomic Scale Modellingsupporting
confidence: 61%
“…UB 2 enriched in 11 B has been the source of burgeoning interest as a fuel material, as a result of its physical and neutronic properties. Recent modelling and experiment suggests that UB 2 may be a significant ATF candidate in its own right [6,7,8] with a uranium density of 11.6 g/cm 3 [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, DFT calculations predict a metallic structure for UO 2 until the additional localization term is included and thereby creates a gap in the electronic band structure [34]. Authors who have previously performed DFT calculations on UB 2 have justified using either a value of 2.0 eV for the Hubbard parameter (based on lattice parameters) [35], or excluded the parameter due to an incorrect prediction for the enthalpy of formation [15]. However, it has been shown experimentally that the 5 f electrons of UB 2 are itinerant due to the small U-U distance, which creates a large ff overlap [36].…”
Section: Methodsmentioning
confidence: 99%
“…It is a common structure shared with many other diborides including ZrB 2 , which is also used as a burnable absorber in some nuclear fuel designs [14]. Previous work has shown that UB 2 does not accommodate any significant deviations in stoichiometry and can therefore be considered a line compound in a similar manner to U 3 Si 2 [15] and ZrB 2 [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, the commercial production of enriched boron-10 for use in control rods necessarily produces material enriched in boron-11 as a by-product, which has a very small neutron cross section. There is currently renewed interest in UB 2 fuel concepts, most notably though atomic scale modelling to predict physical properties [4,6].…”
Section: Introductionmentioning
confidence: 99%